Tracing the Traces of Kinship Politics (Anthropological Reflection) - Ade Yusuf Ferudyn (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The phenomenon of dynastic politics or kinship politics is not only found at the national level, but also occurs at the regional level down to the grassroots level. This paper is a literature study that uses qualitative methods with a descriptive approach from an anthropological historical perspective regarding the traces of dynastic/kinship politics in Indonesia. The results of this study found that the traces of dynastic politics in Indonesia appear to have existed since the royal era which was specifically carried out by the representatives of the king, namely royal officials. In the ethnography of Nordholt (1987) and Koentjaraningrat (1994), it is these royal representatives who actually apply kinship politics by mystifying themselves as minor kings by exploiting the people's belief that kings are incarnations of gods. Their position as deputy king is used as a legitimacy tool to implement dynastic politics, namely by making family members the successor to power as minor kings who also cannot be opposed by the people. In ethnography Shiraishi (2001) suggests the construction of 'father-son' relations in government during the New Order era. The relationship constructed with this 'father-child' pattern places the father in a powerful and superior position, while the child must become an obedient and 'good' person by following various rules and teachings set by the 'father'. The power relation in this context is centered on the paternal genealogy. It was here that the culture of paternalism developed rapidly and was accepted as a matter of course and considered common. 'Family' is constructed as a network, this network is continuously formed and expanded, so that no one can live without relying on personal relationships whose effects are also being felt to this day. Kata Kunci: Dynastic Politics, Kinship Politics